Self‐Stigma in Schizophrenia: A Concept Analysis. Issue 4 (8th January 2014) - Omori, Yoshimi; Mori, Chizuru; White, Ann H.
<x xml:space="preserve">Abstract</x> Purpose This study aimed to clarify the phenomenon and definition of self‐stigma in schizophrenia. Conclusion Self‐stigma in schizophrenia affects patients' well‐being and attitudes to treatment. Although stigma and self‐stigma have interactive and different characteristics, theses definitions are not clearly distinguished. Mental illnesses may have different stereotypes but are treated equally in some studies. Lack of awareness of illness is a common feature in schizophrenia but has not been focused in self‐stigma studies. Practice Implication Further studies are needed to clarify the phenomenon of self‐stigma in people with schizophrenia and to develop interventions targeted at reducing self‐stigma. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Omori </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> Mori </boxed-text> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> White </boxed-text>